Should rape kit testing be prioritized by victim–offender relationship?: empirical comparison of forensic testing outcomes for stranger and nonstranger sexual assaults - Campbell, Rebecca Moira (Criminology & public policy, 2016)
This study examined the DNA forensic testing outcomes from 894 previously untested sexual assault kits (SAKs) from Detroit, Michigan. At issue was how many of these SAKs would produce DNA profiles eligible for upload into CODIS (Combined DNA Index System), the national forensic DNA database maintained by the Federal Bureau of Investigation, and then how many would produce CODIS hits (DNA matches) to other crimes. Fifty‐four percent of the SAKs associated with stranger‐perpetrated sexual assaults yielded CODIS‐eligible DNA profiles, producing 156 CODIS hits (DNA matches) and 51 hits matched prior sexual assault offenses in CODIS (i.e., serial sexual assault hit). Forty percent of the SAKs from nonstranger rapes had CODIS‐eligible profiles, producing 103 CODIS hits and 18 serial sexual assault hits. CODIS entry rates and CODIS hit rates were equivalent between stranger and nonstranger SAKs; serial sexual assault hit rates were significantly higher for stranger SAKs.